Quantifying the Seawater Sulfate Concentration in the Cambrian Ocean - Zhu, Guangyou; Li, Tingting; Huang, Tianzheng; Zhao, Kun; Tang, Wenbo; Wang, Ruimin; Lang, Xianguo; Shen, Bing (Frontiers in Earth Science, 2021)
Although bilateral animals might have first evolved in certain ‘sweet spots’ in the last 10 million years of Ediacaran (550-541 Ma), the Cambrian Explosion requires sufficiently high level of oxygen (O2) in the atmosphere and diverse habitable niches in the substantively oxygenated seafloor. However, previous studies indicate that the marine redox landscape might be temporally oscillatory and spatially heterogeneous, suggesting the decoupling of atmosphere oxygenation and ocean oxidation. The seawater sulfate concentration is controlled by both the atmospheric O2 level and the marine redox condition, with sulfide oxidation in continents as the major source, and sulfate reduction and pyrite burial as the major sink of seawater sulfate. It is thus important to quantify the sulfate concentration in paleoceans. In this study, we measured the Fe speciation and pyrite sulfur isotopes of black shale samples from the Yurtus Formation (the Cambrian Series 2) in the Tarim Block, northwestern China. A numerical model is developed to calculate the seawater sulfate concentration using the Fe speciation and pyrite sulfur isotope data. We first calibrate some key parameters based on observations from modern marine sediments. Then the Monte Carlo simulation is applied to reduce the uncertainty raised by loosely confined parameters. Based on the geochemical data from both Tarim and Yangtze blocks, the modeling results indicate the seawater sulfate concentration of 8.9 14 mM, suggesting the seawater sulfate concentration was already 1/3 to 1/2 of the modern level. This result is consistent with the enhanced terrestrial sulfate input and widespread ocean oxygenation in the eve of Cambrian explosion.